Comparative Analysis of Installed and Actual Pump Power in Bilge and Ballast Systems: Study Case on 60 m Buoy Laying Vessel - Rodlian Jamal Ikhwani; Nurcholik, Samsu Dlukha; Saputra, Muhammad Rizky; Hidayat, Taufik; Syahab, Husein (Naval Architecture Department, Kalimantan Institut of Technology, 2024)
The piping system of a ship is an essential system that is crucial for the ship's operation. An example of tasks related to the ship's piping system is the design of the system itself. When designing a piping system, certain assumptions are made in calculating the pump power. As a result, the installed pump power is often greater than the actual pump power needed. In this thesis, the actual pump power in the bilge and ballast piping system of a 60 m buoy laying vessel needs to be analyzed. To achieve this, comprehensive and detailed data collection of the piping system is required. Then, the piping system must be drawn in full detail using 3D software to match the actual installation of the piping system. After that, the actual pump power for the piping system can be calculated. The calculated pump power is 5.79 kW, with the pump specifications being an centrifugal pump model with an output of 7.5 kW, chosen due to selecting a pump power approximately 16% lesser than the existing power.